The information and communication technologies in the laboratories of educational practice - Fávero, Altair Alberto; Possel, Bianca (Universidade Estadual de Campinas, 2018)
This is a review of the book The ICTs in the Labyrinths of Educational Practice by Arnaldo Nogaro and Elisabete Cerutti published in 2016 by Editora CRV de Curitiba. The work is divided into 7 chapters, in addition to the final considerations, being: Chapter 1 - Learning and teaching: the work of teachers in complex and cybercultural society; Chapter 2 - Anthropological changes resulting from the use of ICTs: what is yet to be known and to come? Chapter 3 - ICTs as a contribution to a research-oriented educational practice; Chapter 4 - Learning to use ICT as tools for the practice of research in education; Chapter 5 - Reflections on teacher training in cyberculture; Chapter 6 - Digital technologies and the lesson: trends in educational practices in cyberculture; Chapter 7 - Interactive practices in higher education: between partnership pedagogy and hybrid teaching; And the final considerations - Between the labyrinths of education and technologies: possible paths and necessary reflections.